APOPHYLLITE (001) SURFACE ALTERATION IN AQUEOUS SOLUTIONS STUDIED BY HAFM - Aldushin K.; Jordan G.; Rammensee W.; Schmahl W.W.; Becker H.W. (My University, 2004)
Depending on pH and temperature, two different types of surface reactions occur on the apophyllite (001) surface in aqueous HCl-solutions at temperatures from 20 to 130 °C. At low pH, laterally spreading hillocks cover the surface. The hillocks are softer than the pristine surface, chemical analysis shows a depletion in Ca + K, and the spreading velocity of hillocks depends on pH. This indicates a change in chemical bond strength, non-stoichiometric dissolution and a mechanism involving protons. External disturbances such as the AFM scanning tip cause the upper surface layers to peel off revealing that the active sites of hillock formation are between the silicate layers of apophyllite. The observed process can therefore be described by a penetrative ion-replacement reaction which proceeds well below the surface monolayer. By this ion-replacement, the silicate layers eventually become destabilised. The observed reaction, therefore, is equivalent to an incongruent dissolution process. Despite structural similarities, this process is only superficially similar to the ion-exchange occurring in clay minerals or zeolites. In these minerals, the structural backbone is not destabilized. At a more neutral pH and high temperatures, step retreat and etch pit formation can be observed on the apophyllite (001) surface thus indicating a more congruent dissolution mechanism.
Keywords: apophyllite